Komparasi Peta Citra Satelit dengan Hasil Pemetaan Desa Gendayakan melalui Program Data Desa Presisi - Rosma Dian Pertiwi; Trevi Marisa; Wisnu Firmansyah; Kusumaningdyah Nurul Handayani; Eksa Rusdiyana (Universitas Muhammadiyah Surakarta, 2023)
The mapping activities in Gendayakan Village through the Data Desa Presisi (DDP) program have the aim to get an accurate picture of the situation and condition of the village. This program uses a combination of approaches such as spatial, census, and participatory. This program involves the participation of the community and the village government of Gendayakan. The method used is a Drone Participatory Mapping (DPM) with the steps carried out, namely (1) The first workshop as an initial socialization of DDP to the villagers; (2) training and capacity building; (3) village image data collection; (4) digitizing to identify village datas; (5) census with MERDESA application by enumerators; (6) analysis and compilation of spatial data using artificial intelligence in the MERDESA application; (7) the second workshop to present the results of the program work accountability. In practice, residents and village governments play an active and cooperative role so as to facilitate the work process. The results obtained in the DDP program include: (1) conveying the urgency of village mapping and the problems faced by the village to the government and residents of the Gendayakan village, (2) five village basic maps that are accurate and able to show the thematic village potential as needed. The impact of this program is to increase awareness and understanding of the community towards mapping and village problems such as village boundaries, distribution of settlements, distribution of infrastructure, and other problems. Mapping is very important and is expected to be followed up by the village government.